2018
DOI: 10.3389/fpls.2017.02246
|View full text |Cite
|
Sign up to set email alerts
|

Soybean NADP-Malic Enzyme Functions in Malate and Citrate Metabolism and Contributes to Their Efflux under Al Stress

Abstract: Malate accumulation has been suggested to balance Al-induced citrate synthesis and efflux in soybean roots. To test this hypothesis, characteristics of Al-induced accumulation and efflux of citrate and malate were compared between two soybean genotypes combining a functional analysis of GmME1 putatively encode a cytosolic NADP-malic enzyme. Similar amounts of citrate were released, and root elongation was equally inhibited before 8 h of Al treatment of Jiyu 70 and Jiyu 62 cultivars. Jiyu 70 began to secrete mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…In fact, mitochondrial malate and citrate concentrations have been demonstrated to improve Al tolerance in tobacco (Nicotiana tabacum), papaya (Carica papaya) and soybean (Glycine max) (De la Fuente et al 1997;Zhou et al 2018). Thus, the canalization of the metabolic flux to improve only malate and citrate concentrations suggests their central role in the enhancement of plant Al tolerance (Nunes-Nesi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mitochondrial malate and citrate concentrations have been demonstrated to improve Al tolerance in tobacco (Nicotiana tabacum), papaya (Carica papaya) and soybean (Glycine max) (De la Fuente et al 1997;Zhou et al 2018). Thus, the canalization of the metabolic flux to improve only malate and citrate concentrations suggests their central role in the enhancement of plant Al tolerance (Nunes-Nesi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…GmME 1 encodes a cytoplasmic ME that helps to increase the concentrations and efflux of malate and citric acid in the body, thereby improving aluminum resistance in plants and helping them to adapt better to the conditions in which they live. 41 Moreover, NADP-ME is also an important player in plantbased defense in Arabidopsis. After pathogen-associated molecular patterns (PAMPs) treatment and pathogen infection, total NADP-ME activity and NADP-ME2 transcript levels are enhanced, and NADP-ME2 loss-of-function mutants (nadp-me2) shows enhanced susceptibility.…”
Section: Relationship Between Me and Plant Stress Resistancementioning
confidence: 99%
“…In recent years, there have been more and more reports on the use of soybean hairy root transformation to verify the function of the soybean Al resistance gene. For example, the dyed GmME1-OX hairy root tip was shallow, and the content of Al was low, indicating strong Al resistance [49]. After Al treatment, the hairy roots of over-expression were found to have the shallow color compared to the control, with the deep color observed of RNAi roots compared to the control, which showed that the Al ion content of GsGIS3-OX hairy root was lower than control ( Figure 6).…”
Section: Discussionmentioning
confidence: 96%